Disease activity, burden and suffering in patients with ulcerative colitis in the UK cohort recruited into the global ICONIC study. Issue 1 (22nd June 2022) - Bhala, Neeraj; Hart, Ailsa; Watts, David; Lewis, Stephen; Ghosh, Subrata; Hansell, Chris; Ahmad, Tariq; Van Haaren, Stijn; Sensky, Tom
Abstract : Objective: The Understanding the Impact of Ulcerative Colitis and Its Associated Disease Burden on Patients (ICONIC) was a 2-year, global, prospective, observational study assessing disease burden in adults recently diagnosed (≤36 months) with ulcerative colitis (UC) receiving routine outpatient care, irrespective of disease severity or treatment. A subanalysis was conducted to understand the UK perspective. Design/method: All eligible consenting patients enrolled in ICONIC from the UK were included in the subanalysis of patient-reported and physician-reported outcomes at baseline and year 2 (Y2). Results: Sixty-three UK patients were included (mean age 43.4 years, 58.7% female). At baseline and Y2, the mean (±SD) Simple Clinical Colitis Activity Index (SCCAI) scores were 3.6 (±3.3) and 1.5 (±1.5); Patient Modified Simple Clinical Colitis Activity Index (P-SSCAI) were 4.9 (±4.0) and 2.6 (±2.6), respectively. Physician-reported Pictorial Representation of Illness and Self Measure (PRISM) median scores (assessing inverse of suffering) were 3.5 (IQR 2.0–6.8) at baseline and 5.5 (IQR 3.6–6.9) at Y2; patient-reported PRISM scores were 4.7 (IQR 2.6–6.9) and 5.4 (IQR 3.2–8.0), respectively. At baseline, SCCAI and P-SCCAI were strongly correlated (r=0.86, p<0.0001), and patient-reported and physician-reported PRISM scores moderately correlated (r=0.67, p<0.0001). At Y2, moderate correlations were observed (SCCAI vs P-SCCAI: r=0.72, p<0.0001; patient-reported vs physician- reported PRISM: r=0.60, p<0.0001). Rating Form of IBD Patient Concerns scores indicated patients' greatest concerns were with energy level, having an ostomy bag and effects of medication (baseline scores >3.0). Conclusions: These findings demonstrated the multifaceted burden of disease in patients recently diagnosed with UC in the UK. Agreement between patients and physicians on disease activity/severity varied according to the instrument used.